Coupling coordination and obstacle factors between tourism and the ecological environment in Chongqing, China: a multi-model comparison. Issue 7 (3rd July 2021) - Zhang, Fengtai; Sun, Changcheng; An, Youzhi; Luo, Yonggang; Yang, Qing; Su, Weici; Gao, Lei
ABSTRACT: This paper constructed the tourism and eco-environment index system, calculated the coupling and coordination relationship between them in Chongqing, from 2000 to 2017, by comparing 9 combination models; and identified the main obstacles through the obstacle model. The results showed that: (1) The comprehensive weighting method (CWM) has the highest accuracy, the coupling coordination mode (CCDM) is more adaptable; the CWM-CCDM is the most suitable. (2) The coupling degree changed from antagonism to run-in phase. (3) The coupling coordination degree improved annually, is in moderate coordination stage currently. (4) The tourism had greater obstacles; the main obstacles vary with time.